Characterization of the patellar tendon reflex response using an indigenously developed system and implementation of a strategic protocol to assess its clinical usefulness - S.K. Kareem; Dilara K; K.N. Maruthy; Priscilla Johnson; A.V. Siva Kumar (Elsevier, 2021)
Introduction: Deep tendon reflex evaluation is a part of the neurological examination and a wide variety of neurological and neuromuscular disorders manifest alterations in deep tendon reflex responses. Conventional methods to assess tendon reflexes in clinical practice are subjective and provide categorical data that might not be adequate in the interpretation. Hence, a quantitative tool is warranted to provide an objective outcome of tendon reflex assessment. The goal of this work was to use an indigenously designed method to characterize the tendon reflex responses. Materials & methods: A cross-sectional study was undertaken in 40 healthy subjects aged between 20 and 45years. Assessment of the tendon reflex was performed using wearable biosensors to characterize it into quantitative variables. A strategic protocol was followed to test the accuracy and repeatability of the outcome. Results: Analysis of phase - I results of the subjective assessment showed high interrater variability and significant bilateral PTR test variability. Whereas the results of the objective assessment showed that the bilateral PTR test variability is minimal by both the assessors. However, the results of all quantified PTR test variables showed an insignificant inter-observer variability except for T 1, TTE and PEAD (p < 0.05*). Conclusion: The findings of this study suggest that quantified tendon reflex using wearable biosensors could provide a piece of valuable information during neurological examination in clinical settings. The proposed tendon reflex quantification tool is non - invasive, portable and inexpensive that can be used for field studies in different clinical conditions.